Hepatoprotective Effect of Polysaccharides Isolated from Dendrobium officinale against Acetaminophen-Induced Liver Injury in Mice via Regulation of the Nrf2-Keap1 Signaling Pathway. (18th July 2018) - Lin, Guosheng; Luo, Dandan; Liu, Jingjing; Wu, Xiaoli; Chen, Jinfen; Huang, Qionghui; Su, Lingye; Zeng, Lei; Wang, Hongfeng; Su, Ziren
Abstract : The effect of polysaccharides isolated from Dendrobium officinale (DOP) on acetaminophen- (APAP-) induced hepatotoxicity and the underlying mechanisms involved are investigated. Male Institute of Cancer Research (ICR) mice were randomly assigned to six groups: (1) control, (2) vehicle (APAP, 230 mg/kg), (3) N -acetylcysteine (100 mg/kg), (4) 50 mg/kg DOP, (5) 100 mg/kg DOP, and (6) 200 mg/kg DOP. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in the serum and glutathione (GSH), malondialdehyde (MDA), catalase (CAT), total antioxidant capacity (T-AOC), myeloperoxidase (MPO), and reactive oxygen species (ROS) levels in the liver were determined after the death of the mice. The histological examination of the liver was also performed. The effect of DOP on the Kelch-like ECH-associated protein 1- (Keap1-) nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway was evaluated using Western blot analysis and real-time polymerase chain reaction (PCR). The results showed that DOP treatment significantly alleviated the hepatic injury. The decrease in ALT and AST levels in the serum and ROS, MDA, and MPO contents in the liver, as well as the increases in GSH, CAT, and T-AOC in the liver, were observed after DOP treatment. DOP treatment significantly induced the dissociation of Nrf2 from the Nrf2−Keap1 complex and promoted the Nrf2 nuclear translocation. Subsequently, DOP-mediated Nrf2 activation triggered the transcription and expressions of the glutamate–cysteine ligase catalytic (GCLC) subunit, glutamate–cysteine ligase regulatory subunit (GCLM), heme oxygenase-1 (HO-1), and NAD(P)H dehydrogenase quinone 1 (NQO1) in APAP-treated mice. The present study revealed that DOP treatment exerted potentially hepatoprotective effects against APAP-induced liver injury. Further investigation about mechanisms indicated that DOP exerted the hepatoprotective effect by suppressing the oxidative stress and activating the Nrf2−Keap1 signaling pathway.